PENERAPAN KOMUNIKASI SBAR (SITUATION, BACKGROUND, ASESSMENT, RECOMENDED) OLEH PERAWAT SAAT HANDOVER DI RUANG RAWAT INAP MURNI TEGUH MEMORIAL HOSPITAL - Elsaria Tinambunan; Seriga Banjarnahor (PT. Hasba Edukasi Mandiri, 2025)
Background: Patient safety has become a global issue that is discussed in various hospitals. There are still many unexpected incidents (KTD), near-injury incidents (KNC) which still frequently occur, and sentinel incidents due to miscommunication. Objective: To determine the application of SBAR communication during handover for nurses at Murni Teguh Hospital, Medan. Method: the type of research design used is descriptive, with a total sampling method of 20 respondents. The instrument used was a questionnaire sheet adopted from the PPSDMK Agency of the Ministry of Health of the Republic of Indonesia in 2017. Results: The research results showed that the implementation of SBAR communication at 6 SOUTH Murni Teguh Memorial Hospital was in the effective category for 20 people (100%). Conclusion: This shows that the majority of nurses implement SBAR communication during handover at Murni Teguh Hospital in Medan. It is hoped that respondents will increase their application of SBAR information communication to improve the quality of service to patients.